2019
DOI: 10.1021/acsinfecdis.8b00338
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Proteomic Analysis Reveals Parasite-Specific Protein Alterations in Macrophages Following Leishmania amazonensis, Leishmania major, or Leishmania infantum Infection

Abstract: Leishmania is an obligate intracellular parasite known to modulate the host cell to survive and proliferate. However, the complexity of host-parasite interactions remains unclear. Also, the outcome of the disease has been recognized to be species-specific and dependent on the host's immune responses. Proteomics has emerged as a powerful tool to investigate the host−pathogen interface, allowing us to deepen our knowledge about infectious diseases. Quantification of the relative amount of proteins in a sample ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…Despite the different experimental conditions and setup, heat-shock and Tryparedoxin related proteins were differentially regulated in 17 studies, indicating that those proteins are often modulated in the parasite. Moreover, several proteins were consistently identifiable and also to be similarly modulating in studies with similar experimental conditions [ 42 , 40 , 41 ]. Only three studies explored the host response (human subjects) during Leishmania infection.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite the different experimental conditions and setup, heat-shock and Tryparedoxin related proteins were differentially regulated in 17 studies, indicating that those proteins are often modulated in the parasite. Moreover, several proteins were consistently identifiable and also to be similarly modulating in studies with similar experimental conditions [ 42 , 40 , 41 ]. Only three studies explored the host response (human subjects) during Leishmania infection.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the study reported U6 snRNA-associated Sm-like protein and heat repeat-containing protein 3 to be precisely up-regulated in infection with L. major , while protein tweety homolog 3, phosphatidate cytidylyltransferase, and macrophage metalloelastase to be precisely up-regulated in infection with L. amazonensis . Overall, the studies by Negrão et al [ 40 , 42 , 41 ] demonstrated the species-specific protein modulation in Leishmania infection as well as differentiated the host response through LPS inoculation and Leishmania infection. To observe the immune response effects of malnutrition in Leishmania infection, Losada-Barragán et al [ 43 , 44 ] conducted the differential proteomic studies involving malnourished mice.…”
Section: Differentially Modulated Proteins In the Host After mentioning
confidence: 99%
See 3 more Smart Citations